ANALISIS PSIKOLOGIS LUKISAN “IBU DAN KUCINGNYA” oleh GARIS EDELWEISS: Psychological Analysis of the Painting 'Mother and Her Cat' by Garis Edelweiss - Muhayya, Viky (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2024)
Artikel ini memberikan analisis psikologis terhadap lukisan